LncRNA DANCR promotes ABL2-mediated metastasis via decoying of miR-125a-5p in high-risk neuroblastoma - Gao, Mingyou; Cao, Fang; Li, Junling; Zhang, Jun; Xia, Yuren; Tian, Xiangdong; Li, Jie; Wang, Daowei; Lu, Lin; Guo, Yan; Liu, Yuanyuan; Zhao, Qiang; et al. (Frontiers in Oncology, 2026)
BackgroundPatients with high-risk neuroblastoma preferentially present with widespread metastasis and often relapse despite intensive therapy, which is the major cause of death of patients with this cancer. Consequently, identifying the molecular drivers of neuroblastoma metastasis holds significant clinical importance.MethodsHigh-throughput sequencing analysis was performed to evaluate gene expression in neuroblastoma patients. In vitro assays were performed to assess cell proliferation, migration, and invasion, while in vivo models were employed to evaluate tumor metastasis. Additionally, integrative transcriptomic and pathway enrichment analyses were utilized to investigate regulatory pathways and molecular mechanisms.ResultsHigh-throughput sequencing analysis revealed that the long noncoding RNA DANCR was significantly upregulated in high-risk neuroblastoma patients, and its expression correlated with poor prognosis. In vitro functional experiments demonstrated that DANCR promotes the proliferation, migration and invasion of neuroblastoma cells. Moreover, DANCR knockdown inhibited tumor metastasis in vivo. Integrative transcriptomic and pathway enrichment analyses further revealed that DANCR overexpression affects the actin cytoskeleton regulatory pathway. Mechanistically, DANCR functions as an oncogenic competing endogenous RNA (ceRNA) through high-affinity binding to miR-125a-5p, thereby promoting ABL2 expression. This DANCR-mediated regulation promotes the interaction between ABL2 and the cytoskeletal regulator cortactin, which leads to activation of the SSH1-cofilin pathway and then facilitates the formation of lamellipodia, cytoskeletal reorganization and the metastatic ability of tumors.ConclusionIn summary, our findings delineate the DANCR/miR-125a-5p/ABL2/cofilin axis as a critical regulator of cytoskeletal dynamics in neuroblastoma metastasis, offering novel insights for the diagnosis and therapeutic targeting of high-risk neuroblastoma.